The Relationship of Mother's Characteristics With The Incident of Bleeding in the Trimester of Pregnancy for Pregnant Women in the Regional Public Health City of Tanjung Balai City - Pohan, Rostina Afrida; Tanjung, Meni Fuji Astuty; Siringoringo, Erlina Esther Rotua (LLDIKTI Wilayah 1, 2024)
As for becoming common/ public target from this research is to know